Fracture Mechanisms of Micro-Alloy Steel at Elevated Temperature - Abdelhalim, Allaoui; Guedri, Abdelmoumene; Darsouni, Lamia; Belyamna, Mohammed Amine (International Journal of Membrane Science and Technology, 2023)
The objective of this work is to study the hot ductility and fracture mechanisms of micro-alloy steel of industrial production whose initial structural state is a rolling stock. To simulate the thermomechanical treatments imposed we have deformed by tensile our samples after having subjected them to a solution treatment at 1200 °C and a precipitation treatment cycle before deformation. Hot deformations were carried out at a deformation rate of 1.96x10-3 s-1 and temperatures from 700 °C to 1050 °C. By observing our tensile-deformed specimens, we can suggest that there is a link between the damage suffered and the type of fracture that results.